Blinatumomab + ponatinib for relapsed/refractory Philadelphia chromosome-positive acute lymphoblastic leukemia in adults. Issue 3 (23rd February 2021) - Couturier, Marie-Anne; Thomas, Xavier; Raffoux, Emmanuel; Huguet, Françoise; Berthon, Céline; Simand, Célestine; Gallego-Hernanz, Maria-Pilar; Hicheri, Yosr; Hunault Berger, Mathilde; Saillard, Colombe; Leguay, Thibaut; Loiseau, Clémence; et al.
Abstract: We retrospectively examined the results of a new chemo-free approach combining blinatumomab with ponatinib (blina/pona) in 26 relapsed/refractory Philadelphia positive (Ph+) acute lymphoblastic leukemia (ALL) patients. All but one achieved complete morphologic remission, and 23 achieved a complete molecular response. With a median follow-up of 34.4 months, the median overall (OS) and event-free (EFS) survivals were 20 and 15.3 months, respectively. After blina/pona, 8 patients underwent an allotransplant (allo), while among the 18 non-transplanted cases, 15 received ponatinib in maintenance. Fifteen relapse/progressions occurred with a significant difference between allo and non allo cases (12.5% vs 82.3%, p  = 0.003). However, OS and EFS were similar between both groups. Finally, blina/pona was well tolerated with eight reversible neurologic events and three cytokine release syndromes. Prospective studies are needed to properly assess the safety, tolerability and efficacy of the combination therapy.